2023
DOI: 10.3390/ijms241310540
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Biomaterials for Hemostatic Applications: A Review of Recent Advances

Daniela Gheorghiță,
Horațiu Moldovan,
Alina Robu
et al.

Abstract: Hemorrhage is a detrimental event present in traumatic injury, surgery, and disorders of bleeding that can become life-threatening if not properly managed. Moreover, uncontrolled bleeding can complicate surgical interventions, altering the outcome of surgical procedures. Therefore, to reduce the risk of complications and decrease the risk of morbidity and mortality associated with hemorrhage, it is necessary to use an effective hemostatic agent that ensures the immediate control of bleeding. In recent years, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 132 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…However, we demonstrated that these cell behavioral properties could be influenced by the scaffold surface topography and chemical composition [56], as well as mechanical characteristics [57,58]. In this study, we examined the surface effects of three polymeric biomaterials that are known for their potential in tissue engineering: a natural biomaterial, CHI [59], and two synthetics, PCL [60] and PLLA [61]. These biomaterials have been used for spinal cord regeneration studies [38,[48][49][50][51][52]], but it is unknown which biomaterial has the more suitable characteristics for SCC and NPCs development.…”
Section: Discussionmentioning
confidence: 99%
“…However, we demonstrated that these cell behavioral properties could be influenced by the scaffold surface topography and chemical composition [56], as well as mechanical characteristics [57,58]. In this study, we examined the surface effects of three polymeric biomaterials that are known for their potential in tissue engineering: a natural biomaterial, CHI [59], and two synthetics, PCL [60] and PLLA [61]. These biomaterials have been used for spinal cord regeneration studies [38,[48][49][50][51][52]], but it is unknown which biomaterial has the more suitable characteristics for SCC and NPCs development.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the different inherent characteristics, some polymers are more promising in specific areas of application. For example, due to its cationic properties, chitosan can cause the aggregation of erythrocyte and platelets, making it more suitable for hemostasis [216]. Hyaluronic acid is a main component of the ECM, and, therefore, hyaluronic acid is more promising for cell delivery than other polymers [82,124].…”
Section: Challenges and Perspectives Of Biodegradable Polymer-based T...mentioning
confidence: 99%
“…These complications significantly contribute to the escalation of healthcare expenses and pose a life-threatening danger to the patient [7][8][9][10]. Therefore, to mitigate the risk of complications and reduce the chances of morbidity and mortality associated with a hemorrhage, it is crucial to use an effective hemostatic agent that can promptly achieve bleeding control [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a significant interest in promoting hemostasis, preventing wound infections, and enhancing the wound healing process, when it comes to hemostatic agents. These aspects should be given serious consideration in the development and engineering of hemostatic materials [11,30,31].…”
Section: Introductionmentioning
confidence: 99%